Pemberdayaan Kelompok Masyarakat Pesisir melalui Budi Daya Rumput Laut Metode Vertikultur di Kawasan Perdesaan Tumbuh Lestari Desa Rambu Rambu, Kabupaten Konawe Selatan - Nur Irawati; Asriyana Asriyana (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Rambu-rambu Village is one of the villages clustered within the Tumbuh Lestari rural area of North Konawe District. The main purpose of this project was to empower the coastal community groups in Rambu-rambu Village through the introduction of in-cage verticulture farming of seaweed. The project was carried out within the scheme of Community Service Program (PKM/Pengabdian Kepada Masyarakat) funded by the University of Halu Oleo. The project lasted for 30 days from 29 June to 28 July 2019. The activity consisted of three stages, are initial dissemination activity, preparation of the training, and implementation of training of seaweed culture. The project involved 20 students of the University of Halu Oleo and 42 people from fishermen, fisherme wifes, and farmer groups. Before the training was conducted 66.7% of the participants did not have the knowledge and after the training 71.4% of the respondents gained an understanding regarding the seaweed verticulture farming method. The improvement of skill was also evident where before the training, 81% of the participants were not able to do seaweed farming method and after the training, 61.9% of the participants were capable or skilled of repeating the seaweed verticulture method. The increased knowledge of the participants could be described from their ability to clearly explain types of seaweed species used, the benefits of seaweed, and the characteristics of high quality of seaweed seed. The improved skill of the participants were also observed from their skill in constructing the seaweed raft and seaweed net cage, tying up the seaweed seed, and conducting the observation of water quality condition in the location of seaweed farming. The result of this activity showed an increased of knowledge and skill of the trained participants regarding seaweed farming using verticulture method.